Jahiliyah Perspektif Hadis - Fitri_Azzahra, Annisa (Khulasah : Islamic Studies Journal, 2024)
The term jahiliyah refers to the state of the Arab world before the arrival of Islam. It was a state of ignorance about Allah, the Prophet, and the religious laws, as well as various other offenses. The purpose of this study is to examine the meaning of jahiliyah and the understanding of the hadith of the four things of jahiliyah mentioned by the Prophet. Data were collected through literature research with a qualitative approach. The traditions were collected using the takhrīj ḥadīth method that refers to the book of the original source of the tradition. This study found that the term jahiliyah does not only refer to a certain time, place, or people, but even more than that. Jahiliyyah is a representation and attitude that deviates from the commands of Allah Swt. The hadith related to ignorance is found in several books including the book of Ṣaḥīḥ Muslim, Sunan al-Tirmiżī, and Musnad Ahmad ibn Hanbal. The Hadīth explains four things of ignorance, including pride in position, which is a great ignorance, because there is no pride except obedience to Allah Swt, and there is no glory for anyone except for the sake of Allah Swt. Then denouncing lineage, saying that no one can benefit from his lineage. Furthermore, asking for rain with the stars, in essence, humans are obliged to attribute all favors to the giver, namely Allah Swt. Then mourning the dead with crying, screaming, and wailing is kufr and is forbidden by Allah Swt.